Deconstructing the Feminine : Psychoanalysis, Gender and Theories of Complexity. - Leticia, Glocer (Karnac Books, 2007)
The guiding thread of this theoretical review is the illumination of the impasses of binary thought and of the essentialist conceptions of women and the feminine. In this trajectory, the author's ongoing dialogue with Freud is connected with one aspect of his way of thinking: multicentred and complex. The text addresses questions relating to love, sexual desire, maternity, beauty and the passing of time and highlights current debates concerning women, the feminine, and sexual difference as well as some controversial topics that have been discussed throughout the history of the psychoanalytic m.